Bibliometric analysis on biobutanol production research trends from 2010-2022 using scopus database - Muhd Arshad Amin,; Hafiza Shukor,; Muaz Mohd Zaini Makhtar,; Mohd Ikhwan Ismail,; Nur Amira Suriaty Yaakop,; Mohamad Danial Shafiq,; Noor Fazliani Shoparwe, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The global demand for biofuels as an alternative energy source is on the rise due to the anticipated decline in fossil fuel (gasoline). Biobutanol, among various biofuels, has garnered significant attention for its advanced features and suitability as an alternative to fossil fuels. Recognizing the importance of understanding research issues and fostering collaborative networks, this bibliometric analysis focuses on synthesizing research trends in biobutanol production over the past 12 years. Examining 357 Scopus-indexed documents, the study shows that over 80% of relevant articles were published after 2010, indicating the recent emergence of literature in this field. Citation analysis identifies publishing trends dating back to 2010, highlighting leading scholars. In 2016, 47 publications in Chemical Engineering were attributed to the field, with Professor Sahaid authoring 12 publications, primarily affiliated with UKM. Chemical Engineering comprised the predominant subject area, with articles constituting 75.07% of total publications. Bioresource Technology was the primary source title, and the keyword Biobutanol was frequently associated with the research (92.16%). UKM led in institutional contributions with 12 publications, while India had the highest total publications at 17.65%, and Malaysia contributed 6.44%. The majority of publications (88.24%) originated from journal publications, and English was the predominant language, accounting for 96.64% of the publications. This paper underscores the recent surge in biobutanol research and the importance of collaborative efforts for further advancements.